2018
DOI: 10.1186/s12866-018-1344-z
|View full text |Cite
|
Sign up to set email alerts
|

The possible molecular mechanisms of farnesol on the antifungal resistance of C. albicans biofilms: the regulation of CYR1 and PDE2

Abstract: BackgroundFarnesol has potential antifungal activity against Candida albicans biofilms, but the molecular mechanism of this activity is still unclear. Farnesol inhibits hyphal growth by regulating the cyclic AMP (cAMP) signalling pathway in C. albicans, and CYR1 and PDE2 regulate a pair of enzymes that are directly responsible for cAMP synthesis and degradation. Here, we hypothesize that farnesol enhances the antifungal susceptibility of C. albicans biofilms by regulating CYR1 and PDE2.ResultsThe resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Chen et al (2018) reported that CYR1 and PDE2 regulate resistance mechanisms against various antifungals in C. albicans biofilms. However, farnesol can diminish the resistance of C. albicans biofilms by regulating the expression of the gene CYR1 and PDE2 [ 74 ]. Yu et al (2012) observed that the sterol biosynthetic pathway may contribute to the inhibitory effects of farnesol, as the transcription levels of the ERG11 , ERG25 , ERG6 , ERG3 , and ERG1 genes decreased following farnesol exposure [ 75 ].…”
Section: Farnesolmentioning
confidence: 99%
“…Chen et al (2018) reported that CYR1 and PDE2 regulate resistance mechanisms against various antifungals in C. albicans biofilms. However, farnesol can diminish the resistance of C. albicans biofilms by regulating the expression of the gene CYR1 and PDE2 [ 74 ]. Yu et al (2012) observed that the sterol biosynthetic pathway may contribute to the inhibitory effects of farnesol, as the transcription levels of the ERG11 , ERG25 , ERG6 , ERG3 , and ERG1 genes decreased following farnesol exposure [ 75 ].…”
Section: Farnesolmentioning
confidence: 99%
“…They have found that a Candida strain carrying a dominant active variant of Ras 1 , which forms hyphae under non inducing conditions, grew as yeast form in presence of farnesol. A recent report suggested that CYR1 and PDE 2 are involved in the molecular mechanism of farnesol on antifungal resistant to Candida biofilms (Chen et al 2018 ).…”
Section: Response Of Human Fungal Pathogen Candida Albicansmentioning
confidence: 99%
“…The maximum combined effect was dependent on farnesol concentration (Katragkou et al, 2015). Chen et al reported that the resistance of C. albicans biofilms to antifungals is associated with the enzymes CYR1 and PDE2, which are responsible for the synthesis and degradation of the cyclic AMP signaling pathway, and that farnesol reduces the antifungal resistance of C. albicans biofilms (Chen et al 2018).…”
Section: Discussionmentioning
confidence: 99%